Analysis of Stress Levels and Their Relationship with Heart Health in the Elderly - Olyvia Rosalia; Dewi Setya Paramitha; Yunita Sari Thirayo; Jean Henry Raule; Gregorius Raditya Indra Prihandana (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the relationship between stress levels and heart health among the elderly using a quantitative cross-sectional approach. The research involved 323 elderly participants aged 60 years and above, selected through proportional random sampling to ensure population representation. Data collection included the Perceived Stress Scale (PSS) to measure stress levels and clinical tests such as blood pressure, cholesterol levels, and electrocardiograms (ECG) to assess heart health. Additional information on demographics and lifestyle factors was gathered through questionnaires. The data was analyzed using descriptive statistics to assess the distribution of stress levels and heart health conditions, as well as correlation tests (Pearson or Spearman) to examine the relationship between stress and heart health. Linear regression analysis was conducted to determine the effect of stress on heart health, considering control variables such as age, gender, and lifestyle factors. The study adheres to ethical research standards, ensuring informed consent and confidentiality of participant data. The findings highlight a significant relationship between high stress levels and poor heart health among the elderly, emphasizing the need for effective stress management interventions to improve cardiovascular outcomes in this population.